Experimental Investigation into a Novel Modular PEMFC Fuel Cell Stack. Issue 2 (11th February 2015) - Scott, P.; Chen, Y.; Calay, R.; Bhinder, F.
Abstract The polymer electrolyte membrane fuel cell (PEMFC), despite being regarded as an ideal replacement to the internal combustion engine, is still not an economically attractive prime‐mover due to a number of key challenges that have yet to be fully resolved; such as degradation to cell components resulting in inadequate lifetimes, specialized manufacturing processes, and poor gravimetric/volumetric energy densities. This paper presents a stack concept which replaces the conventional bipolar plate (BPP), a component that is responsible for a large proportion of stack cost and volume in traditional fuel cell stack designs. The stack architecture compromises of active and passive components which are suited to mass manufacture and maintain functionality that the BPP fulfilled. Furthermore, the design allows the implementation of a fault tolerant system (FTS) which can bypass faulty cells while still ensuring electrical output. The stack architecture is presented and characterized over a number of operating scenarios. The experimental studies suggest that the performance of the new design is similar to that of traditional stacks over a number of operating conditions despite the removal of the BPP and the FTS continued to operate at a desired operating criterion despite the loss of a cell within the stack